Increased platelet reactivity and significant changes in coagulation markers after cavopulmonary connection. Issue 1 (1st January 2001) - Ravn, H B; Hjortdal, V E; Stenbog, E V; Emmertsen, K; Kromann, O; Pedersen, J; Sorensen, K E
Abstract : OBJECTIVE: To evaluate platelet reactivity and coagulation markers after surgical palliation of univentricular hearts. DESIGN AND PATIENTS: Cross sectional survey of 24 patients, median age 11 (range 4–22) years, at 2 (range 0.5–6) years after a total cavopulmonary connection (TCPC; n = 14) or a bidirectional Glenn anastomosis (Glenn; n = 10). MAIN OUTCOME MEASURES: Platelet reactivity and/or coagulation markers were measured in 20 patients (four excluded because of anticoagulant treatment) and compared with 33 healthy controls, median age 12 (range 6–16) years. RESULTS: None of the patients had clinically apparent thromboembolic events. However, increased platelet reactivity was observed ex vivo both after collagen induced platelet aggregation (median 73% (interquartile range 61–84%) in patients, and 61% (47–69%) in controls; p < 0.01), and after ADP induced platelet aggregation (69% (53–77%) in patients, and 56% (40–66%) in controls; p < 0.05). Concentrations of protein S antigen, antithrombin III, and protein C activity were reduced after both TCPC and Glenn. A concomitant decrease was seen in coagulation factor II, VII, X, and factor VII clot activity. CONCLUSIONS: Several abnormalities in the coagulation system were observed after bidirectional Glenn anastomosis, similar to alterations previously described in Fontan operated and TCPC patients. Antithrombotic treatment in these patients is still an unresolved issue, but aspirin is often recommended. This study shows that such a strategy is rational and the results suggest that antiplatelet treatment may be advantageous, either alone or in combination with oral anticoagulant treatment.